Development of Sukuk Musyarakah and Sukuk Istishna Products: Legal Aspects and Potential Implementation in Indonesia - Tuti Nadhifah; Heni Risnawati; Muhammad Dzulhilmi Yazid (Program Studi Ekonomi Islam - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
This study examines the legal architecture and practical feasibility of Sukuk Musyarakah and Sukuk Istisna as sharia-compliant financing instruments in Indonesia, with a specific focus on their application to infrastructure and MSME financing. Methodologically, a qualitative doctrinal and regulatory analysis is employed to synthesize statutory, supervisory, and market governance provisions on sukuk issuance and implementation, while aligning these with sectoral financing needs to identify enabling conditions and constraints. The findings indicate that both instruments are viable and, in certain project configurations, preferable alternatives for mobilizing long-term capital to MSME-linked infrastructure, owing to their risk-sharing mechanisms and asset-backed structures. However, diffusion remains constrained by limited literacy among issuers and investors, uneven market infrastructure, and execution frictions that impede scalability. The study contributes by delineating a coherent legal pathway for structuring Musyarakah and Istisna sukuk within Indonesia’s current framework, mapping policy and market gaps, and proposing operational levers to enhance acceptance and market development. Although the qualitative scope and evolving regulation limit generalizability, the analysis yields actionable implications for regulators, intermediaries, and issuers committed to expanding inclusive, sharia-aligned financing. The originality lies in integrating legal analysis with application-oriented financing insights for MSMEs and infrastructure within Indonesia’s maturing sukuk ecosystem.